Ligand impact on reactive oxygen species generation of Au10 and Au25 nanoclusters upon one- and two-photon excitation - Hussein Fakhouri; Martina Perić Bakulić; Issan Zhang; Hao Yuan; Dipankar Bain; Fabien Rondepierre; Pierre-François Brevet; Željka Sanader Maršić; Rodolphe Antoine; Vlasta Bonačić-Koutecký; Dusica Maysinger (Communications Chemistry, 2023)
Abstract In photodynamic therapy (PDT), light-sensitive photosensitizers produce reactive oxygen species (ROS) after irradiation in the presence of oxygen. Atomically-precise thiolate-protected gold nanoclusters are molecule-like nanostructures with discrete energy levels presenting long lifetimes, surface biofunctionality, and strong near-infrared excitation ideal for ROS generation in PDT. We directly compare thiolate-gold macromolecular complexes (Au10) and atomically-precise gold nanoclusters (Au25), and investigate the influence of ligands on their photoexcitation. With the ability of atomically-precise nanochemistry, we produce Au10SG10, Au10AcCys10, Au25SG18, and Au25AcCys18 (SG: glutathione; AcCys: N-acetyl-cysteine) fully characterized by high-resolution mass spectrometry. Our theoretical investigation reveals key factors (energetics of excited states and structural influence of surface ligands) and their relative importance in singlet oxygen formation upon one- and two-photon excitation. Finally, we explore ROS generation by gold nanoclusters in living cells with one- and two-photon excitation. Our study presents in-depth analyses of events within gold nanoclusters when photo-excited both in the linear and nonlinear optical regimes, and possible biological consequences in cells.